Application and Perspectives of Supercritical Fluid Technology in the Nutraceutical Industry. (9th May 2022) - Li, Lei; Chen, Minyi; Zeng, Yun; Liu, Gang
Abstract: Supercritical fluid extraction (SFE) is an eco‐friendly technology that has attracted a great amount of attention in the food and nutraceutical industries due to its considerable benefits over conventional techniques. It has high selectivity and can be employed to extract heat sensitive, easily oxidized compounds with high efficiency. Less organic solvent is used during extraction, leaving no toxic residues in the product. With these advantages, SFE has been widely applied in bioactive compound extraction from natural plant materials or by‐products. This review summarizes the recent application of SFE in nutraceutical industries including recovery of carotenoids, phenolic compounds, lipids, flavor and fragrance, and decaffeination of tea and coffee. The key parameters affecting SFE are also discussed with focuses on pretreatment, temperature and pressure, flow rate, extraction time, and cosolvent/modifier. Overall, this review builds a comprehensive picture of SFE application in the nutraceutical industry. It is anticipated that this article can provide useful information for researchers to pursue more applications of this technology in the food and nutraceutical industries. Abstract : The current review provides an overview of the recent applications of supercritical fluid extraction (SFE) in nutraceutical industries including recovery of carotenoids, phenolic compounds, lipids, flavor and fragrance, and decaffeination of tea and coffee. The key parameters affecting SFE are also discussed with focuses on pretreatment, temperature and pressure, flow rate, extraction time, and cosolvent/modifier.